Comparing radiolytic production of H2O2 and development of Zebrafish embryos after ultra high dose rate exposure with electron and transmission proton beams. (October 2022) - Kacem, Houda; Psoroulas, Serena; Boivin, Gael; Folkerts, Michael; Grilj, Veljko; Lomax, Tony; Martinotti, Adrien; Meer, David; Ollivier, Jonathan; Petit, Benoit; Safai, Sairos; Sharma, Ricky A.; et al.
Abstract: The physico-chemical and biological response to conventional and UHDR electron and proton beams was investigated, along with conventional photons. The temporal structure and nature of the beam affected both, with electron beam at ≥1400 Gy/s and proton beam at 0.1 and 1260 Gy/s found to be isoefficient at sparing zebrafish embryos.